Extremely low nucleotide diversity in the X-linked region of papaya caused by a strong selective sweep. Issue 1 (December 2016) - VanBuren, Robert; Wai, Ching; Zhang, Jisen; Han, Jennifer; Arro, Jie; Lin, Zhicong; Liao, Zhenyang; Yu, Qingyi; Wang, Ming-Li; Zee, Francis; Moore, Richard; Charlesworth, Deborah; et al.
Abstract Background The papaya Y-linked region showed clear population structure, resulting in the detection of the ancestral male population that domesticated hermaphrodite papayas were selected from. The same populations were used to study nucleotide diversity and population structure in the X-linked region. Results Diversity is very low for all genes in the X-linked region in the wild dioecious population, with nucleotide diversityπ syn = 0.00017, tenfold lower than the autosomal region (π syn = 0.0017) and 12-fold lower than the Y-linked region (π syn = 0.0021). Analysis of the X-linked sequences shows an undivided population, suggesting a geographically wide diversity-reducing event, whereas two subpopulations were observed in the autosomes separating gynodioecy and dioecy and three subpopulations in the Y-linked region separating three male populations. The extremely low diversity in the papaya X-linked region was probably caused by a recent, strong selective sweep before domestication, involving either the spread of a recessive mutation in an X-linked gene that is beneficial to males or a partially dominant mutation that benefitted females or both sexes. Nucleotide diversity in the domesticated X samples is about half that in the wild Xs, probably due to the bottleneck when hermaphrodites were selected during domestication. Conclusions The extreme low nucleotide diversity in the papaya X-linked region is much greater than observed in humans, great apes, and the neo-X chromosome ofDrosophila miranda, which show the expected pattern of Y-linked genes < X-linked genes < autosomal genes; papaya shows an unprecedented pattern of X-linked genes < autosomal genes < Y-linked genes.